2018
DOI: 10.1007/s00405-018-5009-1
|View full text |Cite
|
Sign up to set email alerts
|

ENT audit and research in the era of trainee collaboratives

Abstract: Large surgical audits and research projects are complex and costly to deliver, but increasingly surgical trainees are delivering these projects within formal collaboratives and research networks. Surgical trainee collaboratives are now recognised as a valuable part of the research infrastructure, with many perceived benefits for both the trainees and the wider surgical speciality. In this article, we describe the activity of ENT trainee research collaboratives within the UK, and summarise how INTEGRATE, the UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The expectation of trainees for transparency around their involvement in a TRC and recognition of their inputs has been raised by several TRCs5 15 and in an analysis of TRC-led publications 18. Some TRCs have collaborative authorship policies to acknowledge trainee inputs 5 14. Although our study found some support for this model, others preferred ‘headline’ named authors, in part through concerns about publication requirements for the CCT.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The expectation of trainees for transparency around their involvement in a TRC and recognition of their inputs has been raised by several TRCs5 15 and in an analysis of TRC-led publications 18. Some TRCs have collaborative authorship policies to acknowledge trainee inputs 5 14. Although our study found some support for this model, others preferred ‘headline’ named authors, in part through concerns about publication requirements for the CCT.…”
Section: Discussionmentioning
confidence: 70%
“…The establishment of TRCs, their structure and conduct of trainee-led studies have been described for several clinical specialties,14 15 16 including some of the strategies developed in this research, for example, a consultant champion 5. Consultant support was also highlighted in a recent study of a trainee-led clinical trial involved with the NIHR API scheme 17.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative conducting multicentre research within clinical training and NHS services (Smith et al, 2018). Our author group is working with INTEGRATE on a trainee led national prospective cohort study of adult patients presenting to the NHS with sudden onset SNHL.…”
Section: Uk Ent Trainees Have Recently United In Integrate a National Ent Trainee Researchmentioning
confidence: 99%
“…outcome set is established, a second proposal should be a national collaborative cohort study assessing DNSIs, for example, with the use of a trainee collaborative 101. With data finalised, a consensus study using the Delphi Technique 102 should be used to establish a treatment protocol for DNSIs.4 | CONCLUSIONDNSIs comprise a selection of diseases.…”
mentioning
confidence: 99%